(untitled) (LIS TODAY, 2024)
As one of the first-hand empirical efforts, the paper investigates the outstanding role of the inclusive library formed in the university, examines how they work, structure, and its impacts on cultivating accessibility of students with disabilities. Particularly, the article emphasizes equality rights, policy reforms, and opportunities for approaching institutions of higher education, as well as identifies the practical situations existing. Along with that, an empirical observation was carried out with over 100 websites of libraries in Vietnamese universities including public and private institutions. The findings of the investigation show that the inclusive library contributes significantly to the overall development of people with disabilities, especially in gaining equal accessibility to benefits, rights, policies, and opportunities from society. As a consequence of the state of current existing situations, which directly intervene in the special needs of learners with impairments, the paper makes some recommendations for libraries of Vietnamese universities, such as facilities, library infrastructure, collections and services, activities, etc. Moreover, these practical solutions to practical problems aim to raise further awareness among the government, leaders of parent universities, staff, and non-disabled people with respect to the equal rights and policies of impaired students, regardless of what conditions and where they are. More importantly, they have many more equal opportunities for improving and developing comprehensively their impaired abilities and skills in certain circumstances. Theoretical and practical situations of the findings are considered below.